2000
DOI: 10.1111/j.1572-0241.2000.02243.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal lymphadenopathy in patients with or without previous malignancy: EUS-FNA-based differential cytodiagnosis in 153 patients

Abstract: In patients without previous cancer malignant ML originates from the lung >80%. In those with previous malignancy recurrence of extrathoracic sites is the major cause. Benign lesions and treatable second cancers occur in a significant frequency, emphasizing the need for tissue diagnosis. EUS-FNA is a safe and minimally invasive alternative for cytodiagnosis in the mediastinum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(53 citation statements)
references
References 43 publications
3
46
1
3
Order By: Relevance
“…Also, in contrast to other studies, there were relatively few patients (three out of 52) with a prior history of cancer. In the study by FRITSCHER-RAVENS et al [12], approximately one third of patients (52 out of 153) examined by EUS had a previous diagnosis of cancer. The same study found EUS-FNA to be more accurate when used in patients with a previous diagnosis of cancer compared to patients without (sensitivity 97% with cancer versus 88% without cancer).…”
Section: Discussionmentioning
confidence: 99%
“…Also, in contrast to other studies, there were relatively few patients (three out of 52) with a prior history of cancer. In the study by FRITSCHER-RAVENS et al [12], approximately one third of patients (52 out of 153) examined by EUS had a previous diagnosis of cancer. The same study found EUS-FNA to be more accurate when used in patients with a previous diagnosis of cancer compared to patients without (sensitivity 97% with cancer versus 88% without cancer).…”
Section: Discussionmentioning
confidence: 99%
“…Sonographic signs of benignancy are a hyperechoic core (fat), central calcification (old granulomatous disease), ill-defined edges and an elongated oval shape [67]. Regarding lymph node staging, it has been demonstrated that ultrasound features are not as accurate as aspirates [3] and therefore aspirates are needed.…”
Section: Transoesophageal Ultrasound-guided Fine Needle Aspirationmentioning
confidence: 99%
“…35 Consecutive FNA and appropriate follow-up Savides et al [100] 2000 54 Consecutive FNA and appropriate follow-up Fritscher-Ravens et al [103] 2000 153 Consecutive FNA and appropriate follow-up Vazquez-Sequeiros et al [105] 2001 37 Consecutive Surgery Wallace et al [91] 2001 43 Consecutive FNA and appropriate follow-up Wiersema et al [85] 2001 82 Prospective Surgery Chhieng et al [96] 2001 103 Consecutive Surgery Devereaux et al [22] 2002 49 Consecutive Surgery Catalano et al [92] 2002 62 Consecutive Surgery Schwartz et al [66] 2002 188 Consecutive Surgery Arima et al [95] 2003 58 Consecutive Surgery Pellise et al [23] 2004 11 Consecutive Surgery Kramer et al [86] 2004 81 Prospective Surgery Walsh et al [97] 2005 27 Consecutive Surgery or appropriate follow-up Tournoy et al [88] 2005 67 Prospective Surgery Khoo et al [93] 2006 20 Prospective Surgery Beek et al [87] 2006 43 Prospective Surgery Figure 2A and B, respectively. EUS without FNA had a pooled specificity of 84.6% (95% CI: 83.2-85.9) and with FNA was 96.4% (95% CI: 95.3-97.4).…”
Section: Confirmatory Proceduresmentioning
confidence: 99%